Community empowerment for malaria control and prevention in Kampung Tong Nibong, Sarawak: an intervention study - Hasnor Hadi Asim,; Normawati Ahmad,; Abu Bakar Rahman,; Nik Mansor Ibrahim,; Mohd Nasir Abdullah,; Md Sabtuah Royali,; Albeny Joseph Panting,; Nurashma J,; Ricky Sungom G,; Yusoff Adon, (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Introduction Tong Nibong is a Bidayuh village located at Sarawak Kalimantan border. Since the year 2004 to 2009, a total of 537 cases of malaria were recorded in Serian District of which 14 cases were reported from Kampung Tong Nibong. Community empowerment programme for malaria infection prevention showed tremendous improvement in implementation. This intervention study aims to gauge the effectiveness of community empowerment approach in malaria elimination programme in Kampung Tong Nibong Serian. Methods An intervention study was conducted with pre and post data collection. Data was collected using validated questionnaire by face to face interview. Universal sampling method was used to select respondents from head of household and post data was collected after intervention activities were carried out within a year of study period. Results The study showed significant difference on level of knowledge of respondents on vector of malaria between pre and post data with a P < 0.05. There was significant difference between pre and post data on practices on control and prevention of malaria with a P < 0.05. The same goes to level of positive attitude of respondents towards malaria control. Conclusions In conclusion, the study can be considered successful because there is significant difference in knowledge, attitude and practice among the respondents between pre and post data. This indicates that community empowerment (voluntary participation) measures can be implemented in high risk or endemic areas where malaria is a persistent problem to the community and health institutions faces many limiting factors.